Lorlatinib for the treatment of inflammatory myofibroblastic tumour with TPM4-ALK fusion following failure of entrectinib. Issue 10 (November 2020) - Wong, Han Hsi; Bentley, Helen; Bulusu, Venkata Ramesh; Anyaegbu, Gloria; Watkins, James; Horan, Gail; Hatcher, Helen
Abstract : Inflammatory myofibroblastic tumour (IMT) is a rare malignancy with limited responses to corticosteroids and chemotherapy. About half of cases have activating rearrangements in the ALK gene which could be targeted with ALK inhibitors. A 40-year-old man presented with a large right lung mass and nodal, trapezius and cerebral metastases. Biopsy confirmed IMT with TPM4-ALK fusion. He was treated with prednisolone without clinical benefit. He received the Trk/ROS1/ALK inhibitor entrectinib in a clinical trial but his disease progressed in less than 3 months. Ifosfamide and etoposide in addition to radiotherapy to the brain and chest were administered. Transient improvement in the radiotherapy-treated areas was observed but his disease progressed shortly afterwards on all sites including the development of new adrenal metastasis. Compassionate use of the third-generation ALK inhibitor lorlatinib resulted in excellent partial response on all disease sites after 2 months, followed by a further 6 months of disease stabilisation. Repeat imaging showed slight increase in size of the cerebral metastasis but stable disease elsewhere, for which he was given stereotactic radiotherapy. His disease progressed 3 months later and lorlatinib was substituted with another ALK inhibitor brigatinib but he deteriorated and died shortly afterwards. Our patient tolerated lorlatinib well for 11 months with minimal toxicities, although he developed unilateral right-sided lung consolidation that was probably related to a combination of infection, radiotherapy and lorlatinib, which needed treatment with antibiotics and corticosteroids. This case demonstrates a role of lorlatinib in the treatment of TPM4-ALK -rearranged IMT despite failure of entrectinib.